Comparative Assessment of PASI and Variations of PGA×BSA as Measures of Psoriasis Severity. Issue 4 (September 2017) - Walsh, Jessica A.; Tan, Huaming; Valdez, Hernan; Duffin, Kristina Callis
Background: Commonly used instruments for measuring psoriasis, such as Psoriasis Area and Severity Index (PASI), have limitations, including high complexity. Objective: Determine if PGA×BSA or PGA×√BSA are practical alternatives to PASI for measuring severity and treatment response. Methods: Data from a Phase 3 study in 1, 101 patients treated for moderate to severe psoriasis were used. PASI was the reference standard. Correlations (Pearson coefficients), test-retest reliability (intraclass correlation coefficients), responsiveness to treatment (percentage change and effect size), and correspondence (sensitivity and specificity) were assessed. Results: Correlation coefficients of change (baseline at Week 12) were 0.90 between PASI and either PGA×BSA and PGA×√BSA. ICCs were 0.90. Both instruments demonstrated similar percentage change from baseline and effect sizes. Sensitivities of PGA×BSA and PGA×√BSA were 99% and 95%, and specificities were 76% and 87%, respectively. Conclusions: PGA×BSA and PGA×√BSA had similar measurement properties as PASI. PGA×BSA is a practical alternative to PASI.